If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x/3+12/1=-x/3
We simplify the equation to the form, which is simple to understand
x/3+12/1=-x/3
Simplifying:
+ 0.333333333333x+12/1=-x/3
Simplifying:
+ 0.333333333333x+12=-x/3
Simplifying:
+ 0.333333333333x+12=-0.333333333333x
We move all terms containing x to the left and all other terms to the right.
+ 0.333333333333x + 0.333333333333x=-12
We simplify left and right side of the equation.
+ 0.666666666666x=-12
We divide both sides of the equation by 0.666666666666 to get x.
x=-18
| -[5z-(15z+6)]=6+(9z+0) | | (-11-16)+5= | | 5x/7+12/7=-13/7 | | -4(y+2)=-3y-1 | | 1-6x-13= | | -4(x-6)=-4x+24 | | ln(3x+6)=3 | | 41.5/5 | | 5x+2=8x-4x | | 3y+7x=13 | | 5x+4+4x=31 | | 10.98/3.4 | | x+x+1=x+2+24 | | y=x^2+8x-11 | | 35/8x12/15 | | -1.2r=6.0 | | x^2+8x-11=y | | 4=2y+105 | | 4=2y+70 | | -12r=6.0 | | 4=2y+35 | | 0=81+9y-7x | | -2(4y-7)-2(5y-9)-7y= | | 2x-8y-7x+5y= | | 0=81+9-7x | | 11-2(x+3)=2(1+x) | | P-5=7 | | 7(-w+5)+3(5w+2)=-w+3-3w | | (9x+7)-(7x-5)= | | 37.5q=-.50 | | -3(f-8)=32 | | 2x+5=-7x-13 |